Mast Cells Respond to Candida albicans Infections and Modulate Macrophages Phagocytosis of the Fungus - De Zuani, Marco; Paolicelli, Giuseppe; Zelante, Teresa; Renga, Giorgia; Romani, Luigina; Arzese, Alessandra; Pucillo, Carlo E. M.; Frossi, Barbara (Frontiers in Immunology, 2018)
Mast cells (MCs) are long-lived immune cells widely distributed at mucosal surfaces and are among the first immune cell type that can get in contact with the external environment. This study aims to unravel the mechanisms of reciprocal influence between mucosal MCs and C. albicans as commensal/opportunistic pathogen species in humans. Stimulation of bone marrow-derived mast cells (BMMCs) with live forms of C. albicans induced the release of TNF-, IL-6, IL-13, and IL-4. Quite interestingly, BMMCs were able to engulf C. albicans hyphae, rearranging their α-tubulin cytoskeleton and accumulating LAMP1+ vesicles at the phagocytic synapse with the fungus. Candida-infected MCs increased macrophage crawling ability and promoted their chemotaxis against the infection. On the other side, resting MCs inhibited macrophage phagocytosis of C. albicans in a contact-dependent manner. Taken together, these results indicate that MCs play a key role in the maintenance of the equilibrium between the host and the commensal fungus C. albicans, limiting pathological fungal growth and modulating the response of resident macrophages during infections.